Anti-inflammatory and antioxidant effects of Chaetoglobosin Vb in LPS-induced RAW264.7 cells: Achieved via the MAPK and NF-κB signaling pathways. (January 2021) - Zhang, Hongli; Guo, Qingfeng; Liang, Zhenhua; Wang, Mengke; Wang, Baoguang; Sun-Waterhouse, Dongxiao; Waterhouse, Geoffrey I.N.; Wang, Jinmei; Ma, Changyang; Kang, Wenyi
Abstract: There are few reports on the biological activities of chaetoglobosin Vb (Cha Vb ) (a cytochalasin alkaloid). In this study, we investigated the molecular mechanisms underlying the anti-inflammatory and antioxidant effects of Cha Vb in the RAW264.7 cells stimulated lipopolysaccharide (LPS). LPS stimulation-induced oxidative stress (i.e. increase production of reactive oxygen species (ROS) and decreased expression of antioxidant superoxide dismutase (SOD)) was suppressed after a Cha Vb treatment. Cha Vb could significantly inhibit the upregulated expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) gene and protein induced by LPS whilst attenuating the production of pro-inflammatory cytokines TNF- α, IL-6 and IL-1 β . Such antioxidant and anti-inflammatory effects were achieved through the TLR4-mediated MyD88-dependent signaling pathways ( via suppressing the phosphorylation of p38, ERK, JNK MAPK and translocation of the NF-κB p65 subunit into nucleus), and the TRIF-dependent signaling pathways ( via reducing IFN- β release without inhibiting interferon-regulated factor 3 (IRF3) and IRF7). At 25–100 μM (a concentration range with no cytotoxicity), Cha Vb dose-dependently influenced SOD enzyme activity and phosphorylation of p38, ERK1/2 and JNK, and at 100 μM, likely exerted the greatest inhibition towards LPS-induced oxidative stress and inflammatory response via the MAPK and NF-κB signaling pathway. Highlights: Chaetoglobosin Vb (Cha Vb ) is a bioactive alkaloid from fungal metabolites. Cha Vb can inhibit LPS-induced oxidative stress and inflammatory response. Cha Vb can exert its bioactivities via the MAPK and NF-κB signaling pathway. TRIF-dependent signaling pathways is also activated by Cha Vb via IFN- β.